1990
DOI: 10.1044/jshr.3301.70
|View full text |Cite
|
Sign up to set email alerts
|

Development of Children with Early Language Delay

Abstract: Four children with early language delays (ELD) were compared to a control group of 12 children with respect to their preschool language abilities from age 2 1/2 to 5 years and their verbal skills at the end of Grade 2. The language-delayed children each initially showed severe and broad impairments in syntactic, phonological, and lexical production. Over time, their deficits became milder and more selective, such that normal or nearly normal speech and language proficiency was exhibited by age 60 months. Never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
2
13

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(219 citation statements)
references
References 31 publications
12
190
2
13
Order By: Relevance
“…Also consistent with prior literature (e.g., Nathan et al, 2004;Scarborough & Dobrich, 1990), the present study indicated that children with histories of speech-language difficulties tended to score lower on early reading-related measures. Three findings in regard to the nature of this relation are worth highlighting.…”
Section: Associations With Readingsupporting
confidence: 81%
See 2 more Smart Citations
“…Also consistent with prior literature (e.g., Nathan et al, 2004;Scarborough & Dobrich, 1990), the present study indicated that children with histories of speech-language difficulties tended to score lower on early reading-related measures. Three findings in regard to the nature of this relation are worth highlighting.…”
Section: Associations With Readingsupporting
confidence: 81%
“…The third strength of the present study is its ability to examine phenotypic associations between spoken communication disabilities and early reading-related measures. This latter point is critical in that previous studies have indicated that children with communication difficulties, particularly in the areas of language and articulation/phonology, are at risk for difficulties in reading (Bishop & Adams, 1990;Nathan, Stackhouse, Goulandris, & Snowling, 2004;Scarborough & Dobrich, 1990). Similarly, studies have found that children with reading difficulties are more apt to have spoken language difficulties (e.g., Larrivee & Catts, 1999;Nation, Clarke, Marshall, & Durand, 2004;Scarborough, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] Identification of children at risk for developmental delay or related problems may lead to intervention services and family assistance at a young age when chances for improvement are best. 1 This rationale supports preschool screening for speech and language delay, or primary language impairment/disorder, as a part of routine well-child care.…”
mentioning
confidence: 99%
“…children who fail to produce at least 50 words or a two-word combination of any kind by age two (Rescorla, 1989;Rescorla and Schwartz, 1990;Scarborough and Dobrich, 1990). These studies did not provide clear indications regarding deficits in hearing, intelligence or receptive language ability, although many did attempt to identify predictor variables to assist in distinguishing children who will catch up through their own efforts from those who will require special assistance.…”
mentioning
confidence: 99%